Integrated Traditional Chinese and Western Medicine for the Treatment of Hypertension - Zheng, Yiwen; Chen, Xuebin (Journal of Contemporary Medical Practice, 2024)
This paper aims to explore the advantages of combining traditional Chinese and Western medicine in the treatment of hypertension. By discussing the epidemiology of hypertension, the understanding of hypertension by traditional Chinese and Western medicine, and the treatment methods of traditional Chinese and Western medicine, this paper extensively analyzes the advantages of combining traditional Chinese and Western medicine in improving clinical efficacy, reducing the adverse reactions of single Western medicine, and improving the quality of life of patients. This study helps to provide a more comprehensive and optimized solution for the clinical treatment of hypertension, and to improve the overall health level of patients with hypertension.